Examining the Association between Utilization Management and Downstream Cardiovascular Imaging. (9th April 2014) - Agiro, Abiy; Sylwestrzak, Gosia; Shah, Christiane; Power, Thomas; DeVries, Andrea
<x xml:space="preserve">Abstract</x> Objectives To examine the association of echocardiography utilization management (EUM) program with downstream cardiac imaging utilization. Data Sources/Study Setting Administrative claims data from commercial health plans in Indiana, Ohio, Kentucky, Wisconsin, and Georgia. Study Design Patients undergoing index cardiovascular imaging with no imaging in the preceding year were identified (N = 112, 308). Claims‐derived cardiac risk scores were used for one‐to‐one propensity score matching of patients subject to EUM to patients without EUM (n = 96, 906). Downstream cardiac imaging utilization for 12–24 months postindex imaging was analyzed using generalized linear models and Cox proportional hazards model. Principal Findings Downstream cardiac imaging tests were performed for 10, 630 (21.9 percent) and 12, 012 (24.8 percent) patients in the EUM and non‐EUM groups, respectively. At 12‐month follow‐up, adjusted utilization was 15.2 (95 percent CI, 7.6–22.5) tests per 1, 000 initially tested patients lower in the EUM group (p < .001). The likelihood of obtaining downstream cardiac imaging in the EUM group was 7.0 percent lower than the non‐EUM group (hazard ratio: 0.930; 95 percent CI, 0.897–0.964, p < .001). Conclusions Downstream cardiac imaging is relatively common among commercially insured patients. Every 10 initial diagnostic tests yielded two downstream imaging tests in first 24 months. EUM program was associated with lower volumes of downstream imaging.